2004
DOI: 10.1086/379852
|View full text |Cite
|
Sign up to set email alerts
|

The Giant Branches of Centauri: Multiwavelength Observations of Evolved Stars

Abstract: We present multi-wavelength observations of the northern population of ω Cen from the main-sequence turn-off to high on the red giant branch. We show that the best information about the metallicity and age of the stars can be gained from combining vby, B-I and V-I colors (in the absence of spectroscopy). We confirm our results for the main-sequence turn-off stars: there is at least a 3 Gyr age spread, which may be as large as 5-8 Gyr, as suggested by Hughes & Wallerstein (2000) and Hilker & Richtler (2000). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 46 publications
(43 reference statements)
8
28
1
Order By: Relevance
“…The true age spread in ω Cen and within each of its subpopulations remains a matter of lively debate. Several studies (Hughes et al 2004;Sollima et al 2005b;Stanford et al 2006) concluded that ω Cen enriched itself on a timescale <2-5 Gyr, with each subpopulation being essentially coeval within the uncertainties implied in the analysis (∼1.5 Gyr, see, e.g., Sollima et al 2005b). On the other hand, Johnson et al (2009) presented evidence of different degrees of s-process enrichment among stars in the metal-poor population, which is the one sampled in the present analysis.…”
Section: Discussionmentioning
confidence: 92%
“…The true age spread in ω Cen and within each of its subpopulations remains a matter of lively debate. Several studies (Hughes et al 2004;Sollima et al 2005b;Stanford et al 2006) concluded that ω Cen enriched itself on a timescale <2-5 Gyr, with each subpopulation being essentially coeval within the uncertainties implied in the analysis (∼1.5 Gyr, see, e.g., Sollima et al 2005b). On the other hand, Johnson et al (2009) presented evidence of different degrees of s-process enrichment among stars in the metal-poor population, which is the one sampled in the present analysis.…”
Section: Discussionmentioning
confidence: 92%
“…An age spread of 2-5 Gyr, among the various sub-populations was first found by Hughes & Wallerstein (2000) and Hilker & Richtler (2000), based on the TO region morphology of their high-quality Strömgren photometries and colour-metallicty calibrations. Later several other papers came out based on combinations of high quality photometry and lowresolution spectroscopy (Hughes et al 2004;Hilker et al 2004;Rey et al 2004;Sollima et al 2005b;Stanford et al 2006;Villanova et al 2007), finding again various age dispersions all around 2-5 Gyr. The only studies reporting on age difference below 2 Gyrs are those by Ferraro et al (2004), who find that the SGB-a cannot be fitted with any isochrone younger than the SGB-MP population, and Sollima et al (2005b), who similarly found that the overall age spread of the SGB sub-populations cannot amount to more than 2 Gyr.…”
Section: Towards a Solution Of The Age Spread Problemmentioning
confidence: 96%
“…A large number of photometric and low-resolution spectroscopic studies (Hughes & Wallerstein 2000;Hilker & Richtler 2000;Pancino 2003;Hughes et al 2004;Hilker et al 2004;Rey et al 2004;Ferraro et al 2004;Stanford et al 2006) found age spreads ranging from 2 to 6 Gyr, with a few exceptions and puzzles (see Sect. 5.3, for more details).…”
Section: Introductionmentioning
confidence: 99%
“…The first studies employed photometric metallicity indicators (Hilker & Richtler 2000;Hughes & Wallerstein 2000), soon followed by low-resolution spectroscopic samples (Hughes et al 2004;Hilker et al 2004;Rey et al 2004;Sollima et al 2005b;Stanford et al 2006;Villanova et al 2007), coupled with exquisite new photometric catalogues Bedin et al 2004;Bellini et al 2010), but the puzzle got deeper, Based on observations with the ESO GIRAFFE@VLT, under programme 079.D-0021(A). Also based on literature data obtained with WFI@VLT (programmes 62.L-0345 and 63.L-0439) and FORS@VLT (programme 68.D-0332).…”
Section: Introductionmentioning
confidence: 99%